2003
DOI: 10.1182/blood-2002-08-2548
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin II is essential for sustaining life span of erythrocytes in mice

Abstract: Peroxiredoxins (Prxs) are a family of antioxidant proteins that reduce peroxide levels by using reducing agents such as thioredoxin. These proteins were characterized to have a number of cellular functions, including cell proliferation and differentiation and protection of specific proteins from oxidative damage. However, the physiological roles of the peroxiredoxins have not been determined. To clarify the physiological relevance of this protein type, we generated a mouse model deficient in Prx II, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
275
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(287 citation statements)
references
References 27 publications
9
275
1
2
Order By: Relevance
“…Anaemia was also observed in SOD2 +/+ mice with bone marrow transplanted from SOD2 −/− mice [22,30], but this could be caused by a defect in the process of differentiation to erythrocytes, because SOD2 is absent in erythrocytes. A deficiency in other antioxidative proteins, PrxI [31] and PrxII [32], which catalytically function as thioredoxindependent peroxidases, also causes anaemia by affecting the lifespan of erythrocytes. Since levels of erythrocyte PrxII protein, which is the only Prx member in erythrocytes, were not changed, a contribution of PrxII to anaemia in SOD1 −/− mice is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia was also observed in SOD2 +/+ mice with bone marrow transplanted from SOD2 −/− mice [22,30], but this could be caused by a defect in the process of differentiation to erythrocytes, because SOD2 is absent in erythrocytes. A deficiency in other antioxidative proteins, PrxI [31] and PrxII [32], which catalytically function as thioredoxindependent peroxidases, also causes anaemia by affecting the lifespan of erythrocytes. Since levels of erythrocyte PrxII protein, which is the only Prx member in erythrocytes, were not changed, a contribution of PrxII to anaemia in SOD1 −/− mice is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced lifespan observed in SOD1 −/− ,27 PRX1 −/− ,250 PRX2 −/− 251 and TRX2 +/− 252 models is much more prominent in the SOD1 −/− rodent model,281 indicating that specific key RONS regulatory systems and redox signalling pathways are implicated in the processes of ageing. Moreover, although indistinguishable from WT mice at birth, by 5–8 months of age, SOD1 −/− mice show an accelerated neuromuscular ageing phenotype associated with myofibre atrophy (Figure 5), neurological impairments (Figure 6) and functional deficits 275.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 96%
“…SOD1 −/− ,27 PRX1 −/− ,250 PRX2 −/− ,251 TRX2 +/− 252 and MSRA −/− 253 rodent models show a reduction in lifespan; in contrast, more recent studies have reported no effect of MSRA −/− on rodent lifespan 254. GPX1 −/− ,28, 252 SOD2 +/− ,240 extracellular SOD −/− 255, 256 and MSRB −/− 257 knockout murine models show no effect on lifespan.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
“…Knockout mouse models proved that the lack of peroxiredoxin I resulted in severe haemolytic anaemia, and appearance of lymphomas, sarcomas, and carcinomas [149]. The lack of peroxiredoxin II was also shown to result in haemolytic anaemia [150]. On the other hand, patients having hereditary catalase deficiencies were also shown to be victims of oxidative stress and presented a high prevalence of diabetes [151].…”
Section: Red Blood Cellsmentioning
confidence: 99%